A case of cardiac angiosarcoma and pulmonary tuberculosis; diagnostic challenges and review of literature - Roghayeh Pourkia; Ghasem Faghanzadeh Ganji; Mohsen Vakili Sadeghi; Naghmeh Ziaie; Nahid Rezaeian; Faezeh Dehghani-Tafti; Hossein Ghorbani; Mohammad Mostafa Ansari Ramandi (Babol University of Medical Sciences, 2021)
Background: Patient symptoms and primary investigational methods may be misleading at some points in patient management and can consume a lot of time. Sarcomas are rare malignancies and contribute 1% of all cancers of adult. Case Presentation: A rare case of primary cardiac angiosarcoma is presented, who was first treated because of lung tuberculosis and then with only slight improvement in symptoms, further investigations were done showing right ventricular enlargement and pericardial effusion. Eventually, after ruling out pulmonary embolism and constrictive pericarditis, investigations lead to the diagnosis of primary cardiac angiosarcoma. The patient went under surgery to remove the tumor but he still had residual mass left, leading to chemotherapy and then radiotherapy. Although the tumor has a poor prognosis, our patient has managed to survive a year by now and is doing good for 6 months after radiotherapy. Conclusion: The case describes the importance of having in mind different differential diagnosis in managing patients and the role of multi-modality imaging in guiding diagnosis and treatment.